The Book Cover as a Paratext: Biblia Germanicolatina in the Martynas Mažvydas National Library of Lithuania - Kvizikevičiūtė, Milda (Knygotyra, 2021)
The book cover of Biblia Germanicolatina (1565), which is held at the Rare Books and Manuscrips Unit of the Martynas Mažvydas National Library of Lithuania, is analysed in this paper. This Bible was printed in a 20-volume collection in Wittenberg on request of August the Elect of Saxony (1526–1586). It was printed in the Latin and German languages. This Bible later became a part of various European libraries. Biblia Germanicolatina is analysed in the light of the paratext theory, which as a book history term is first used by French literary theorist Gerard Genette (1987). Genette used this term to describe objects and subjects surrounding the text: text spacing, lettering, book covers and even book advertisements. The analysis is performed using the provenance method, which leads to discovering the origins of the book’s binding and its primary sources. As of right now, five out of the 20 volumes from the collection are known to be held in Lithuanian memory institutions. As a result of this research, we were able to identify the bookbinder from Wittenberg who ordered the plate for tooling in 1564.